INTRODUCTION TO TETHYS-AN INTERDISCIPLINARY GIS DATABASE FOR STUDYING CONTINENTAL COLLISIONS - Khan S.D.; Flower M.F.J.; Sultan M.I.; Sandvol E. (My University, 2006)
The TETHYS GIS database is being developed as a way to integrate relevant geologic, geophysical, geochemical, geochronologic, and remote sensing data bearing on Tethyan continental plate collisions. The project is predicated on a need for actualistic model 'templates' for interpreting the Earth's geologic record. Because of their time-transgressive character, Tethyan collisions offer 'actualistic' models for features such as continental 'escape', collision-induced upper mantle flow magmatism, and marginal basin opening, associated with modern convergent plate margins. Large integrated geochemical and geophysical databases allow for such models to be tested against the geologic record, leading to a better understanding of continental accretion throughout Earth history. The TETHYS database combines digital topographic and geologic information, remote sensing images, sample-based geochemical, geochronologic, and isotopic data (for pre- and post-collision igneous activity), and data for seismic tomography, shear-wave splitting, space geodesy, and information for plate tectonic reconstructions. Here, we report progress on developing such a database and the tools for manipulating and visualizing integrated 2-, 3-, and 4-d data sets with examples of research applications in progress. Based on an Oracle database system, linked with ArcIMS via ArcSDE, the TETHYS project is an evolving resource for researchers, educators, and others interested in studying the role of plate collisions in the process of continental accretion, and will be accessible as a node of the national Geosciences Cyberinfrastructure Network-GEON via the World-Wide Web and ultra-high speed internet2. Interim partial access to the data and metadata is available at: http://geoinfo.geosc.uh.edu/Tethys/ and http://www.esrs.wmich.edu/tethys.htm. We demonstrate the utility of the TETHYS database in building a framework for lithospheric interactions in continental collision and accretion. © 2005 Elsevier Ltd. All rights reserved.
Keywords: CONTINENTAL COLLISION; REMOTE SENSING; TETHYS